A Review of Unemployment, Employment, Participation, and Wage Rates for Aboriginals and Non-Aboriginals — 2007-2019 - Oppenheimer, Robert J. (Journal of Aboriginal Economic Development, 2020)
For Aboriginals in Canada, their employment and participation rates decreased, and their unemployment rate remained the same in 2019. In contrast, non-Aboriginals' unemployment, employment, and participation rates improved. These rates and wage rates are and have historically been more favourable for non-Aboriginals than for Aboriginals. These rates are examined by gender, age, and sector, as well as for Métis and First Nations.